2022
DOI: 10.1051/0004-6361/202243256
|View full text |Cite
|
Sign up to set email alerts
|

SN 2018bsz: A Type I superluminous supernova with aspherical circumstellar material

Abstract: We present a spectroscopic analysis of the most nearby Type I superluminous supernova (SLSN-I), SN 2018bsz. The photometric evolution of SN 2018bsz has several surprising features, including an unusual pre-peak plateau and evidence for rapid formation of dust ≳ 200 d post-peak. We show here that the spectroscopic and polarimetric properties of SN 2018bsz are also unique. While its spectroscopic evolution closely resembles SLSNe-I, with early O ii absorption and C ii P-Cygni profiles followed by Ca, Mg, Fe, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 165 publications
0
13
0
Order By: Relevance
“…Given that the low-level polarisation at +29.0 d implies spherical symmetry, option iii) is unlikely the cause for the continuum polarisation at +3.0 d. Furthermore, Fiore et al (2021) identified broad C ii absorption lines in near-peak spectra of SN 2017gci. As shown in Figure C.6, these lines do not project loops on the Q -U plane -as was seen in SN 2018bsz (Pursiainen et al 2022) -nor do they follow the drawn dominant axis as would be expected if the polarisation properties at +3.3 d were caused by uneven distribution of absorbing material. Thus, option ii) does not seem to be the cause for the tendency of the data and we assume that the polarisation is caused by an inherently aspherical photosphere.…”
Section: Polarimetry Of Sn 2017gcimentioning
confidence: 57%
See 3 more Smart Citations
“…Given that the low-level polarisation at +29.0 d implies spherical symmetry, option iii) is unlikely the cause for the continuum polarisation at +3.0 d. Furthermore, Fiore et al (2021) identified broad C ii absorption lines in near-peak spectra of SN 2017gci. As shown in Figure C.6, these lines do not project loops on the Q -U plane -as was seen in SN 2018bsz (Pursiainen et al 2022) -nor do they follow the drawn dominant axis as would be expected if the polarisation properties at +3.3 d were caused by uneven distribution of absorbing material. Thus, option ii) does not seem to be the cause for the tendency of the data and we assume that the polarisation is caused by an inherently aspherical photosphere.…”
Section: Polarimetry Of Sn 2017gcimentioning
confidence: 57%
“…In the first epoch, the polarisation degree appears to increase towards the red (as in SN 2017gci) and at the second epochs towards the blue, following approxi- The SN showed low level of polarisation at near-peak with no particular line features, but at +185 d the level of continuum polarisation had increased to ∼ 0.8%. Finally, for SN 2018bsz the polarimetric evolution appears to be strongly affected by interaction with highly aspherical CSM (Pursiainen et al 2022), and comparison to SN 2017gci is not fruitful. While the spectropolarimetry shows a low level of polarisation at +29.0 d, the imaging polarimetry at ∼ +55 d shows that the polarisation degree has increased to P ∼ 0.5% in V band.…”
Section: Polarimetry Of Sn 2017gcimentioning
confidence: 97%
See 2 more Smart Citations
“…This discovery allowed Nicholl et al (2016b) to suggest that such bumps may be usual/omnipresent features in SLSNe-I; however, this theory was refuted by Angus et al (2019), who carried out a detailed analysis of SLSNe-I from the Dark Energy Survey and found that only three SLSNe-I showed early bumps in their sample of 14 objects. Later on, PFT12dam (Vreeswijk et al 2017), and potentially SN 2018bsz (e.g., Anderson et al 2018;Chen et al 2021;Gutiérrez et al 2022;Pursiainen et al 2022) and SN 2018hti (Lin et al 2020;Fiore et al 2022) were revealed to show early LC undulations. Gutiérrez et al (2022) examined this topic in detail and found that some SLSNe-I that show smooth LC in their early phase can be characterized by slow photometric evolution (e.g., SN 2007bi, Gal-Yam et al 2009Young et al 2010;LSQ14an, Inserra et al 2017;SN 2015bn, Nicholl et al 2016a, 2016bSN 2017gci, Fiore et al 2021 in their sample).…”
Section: Premaximum Light-curve Undulationsmentioning
confidence: 99%